Impact of Preoperative Imaging (MRI) Modalities on Surgical Planning and Outcome in Prostate Cancer: A Retrospective Analysis - Muhammad, Raza; Patujo, Yassar Hussain; Akhtar, Syed Muhammad Hassan; Shahjehan, Shahjehan; Asghar, Hassan Raza; Adil, Ruqqayia (Journal of Neonatal Surgery, 2025)
Background: Operative planning for the treatment of localised prostate cancer has evolved in tandem with advancing imaging technologies. Limited research has examined how these modifications affect recovery times after surgery. The purpose of this research was to determine if magnetic resonance imaging (MRI) performed before surgery had any effect on the percentage of positive surgical margins (PSMs). Methods: This retrospective comprised of 416 patients of prostate cancer. All the patients were admitted for radical prostatectomy. Patients were divided in two groups. Group I (208) received MRI before radical prostatectomy and group II (208) did not receive MRI before surgery. Post-surgery outcomes were assessed and compared among both groups. Results: We found mean age in group I was 61.32±8.37 years and in group II mean age was 63.14±6.28 years. Mean operative time and blood loss in group I was lower as compared to group II with p <0.003. In both groups PSM was majority occurred at the apex.Both total and prostatic apex PSM were shown to be linked with preoperative MRI status alone, according to multivariate analysis. Postoperative ischemic syndrome was not linked to the surgical strategy, neurovascular bundle sparing method, or perioperative blood loss. Conclusion: MRI is a great tool for detecting and treating PCa right now. It is possible to lessen total PSM, apical PSM, and blood loss with the use of this imaging technology. Further, urologists in the early phases of RP have showed encouraging results using preoperative MRI in reducing the PSM rate